Violence as Communication: A Study of Propaganda of the Deed under Nepal's Maoist Rebellion - Aryal, Kundan (Molung Educational Frontier, 2020)
The study focuses on the communication strategy of an insurgent group. It explores and critiques the acts of violence aimed at creating terror employed by the then Communist Party of Nepal (Maoist) during the 10-year-long "People's War" in Nepal. In course of exploring information and communication system maintained by the party and its outreach strategy during the insurgency, the research outlines the features of the then CPN (Maoist) regarding the communication during the period. The process and tools of internal as well as external communication used by a clandestine organization thus become the major study of the work. The study is based on the literature published by the party and interviews with the Maoist leaders. It reveals a well-functioned communication system was its lifeline of the rebel. The mode of the dissemination of favourable message was mainly based on the violence; they use the term red terror.